Navigating the maze: Qualitative research methodologies and their philosophical foundations. (October 2019) - Bleiker, J.; Morgan-Trimmer, S.; Knapp, K.; Hopkins, S.
Abstract: Objectives: One of the three objectives of the Society and College of Radiographers is the promotion and dissemination of research in radiography and radiotherapy. This article aims to assist in the production of high standard research by explaining how transparency in reporting the underpinning philosophical basis of a qualitative study can be achieved in addition to the more customary descriptions of how data were collected and analysed. Key findings: Unlike their quantitative equivalent, qualitative research methodologies are less well understood and reported in radiography research, in particular the philosophical and epistemological assumptions which underpin the methods used. Conclusion: Demonstrating consistency between the philosophical position taken and the methods used within a study is an important aspect of research quality. Implications for practice: Qualitative research can offer valuable insights into the social, organisational, behavioural and interpersonal aspects of medical imaging practice. These may include wellbeing, attitudes, perceptions and beliefs, leadership, management practices, education, professionalism and a wide range of issues around patients' experiences during medical imaging. Patient care and outcomes can be positively impacted as a result of acquiring these insights.